PEMIKIRAN FILSAFAT IMMANUEL KANT - Abidin, Muhammad Zainal (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
This paper tries to study the philosophical thought of onc of wcsteru greatcst philosopher, that's Immanuel Kant. In studying Ihc pholosphical thought ol'Kant, tlrc writcr bounds in to thrcc things. tjirstly, about Kant and lris thcory ol'knowlcdgc; sccorrdly, about his idcas on dconlology and catcgorical irnperatil'; thirdly, about his opinion on postulat of' practical reason, narrrcly about the fi'ecdom of will, the imortality ol spirit and about thc being t-rl'God. Actually, the philosphical thought of Kant was not out of critics. llerc, the writcr uses the opinion of Flegel aild Maclntyre as to critizc the idcas o[- Kant. llowevcr, as lirr thc writcr, out ol' thc strcngth and lhc wcakncss ol' Kartt's thought, lrc was rcally one of western philosopher who madc thc grcat inllucncc to the prefcrcncc western philosph-v aftcr lrirn.